Indigenous land dispute and law reform in India: lessons for Malaysia / Izawati Wook - Wook, Izawati (2014)
Indigenous land dispute is a continuing issue in Malaysia which needs to be addressed. Apart from the common law recognition of the land rights of the indigenous peoples, the indigenous peoples are increasingly widely recognised as a stakeholder in the natural resources located within their areas. Worldwide, since 1992, there has been a dramatic increase in legislation around the world recognizing the rights of indigenous peoples and communities to forest lands and resources. The surge is seen as a response to the 1992 Earth Summit and its Convention on Biological Diversity that emphasizes the preservation of forests for halting biodiversity loss. An interesting law reform exercise has been done in India. It introduced Scheduled Tribes and Other Traditional Forest Dwellers (Recognition of Forest Rights) Act 2006 (FRA) to address the claim of the indigenous peoples to forest resources. India is relevant as a comparison to Malaysia as both share some common political and legal features. India also directly influenced the development of law in Malaysia. Apart from being common law jurisdictions, it is a developing Asian country with a sizable tropical forest cover. Using a comparative approach, this paper proposes to analyse processes and mechanisms adopted in the relevant law reform in India and its relevance to Malaysia. Comparative perspectives provide models for practical applications of indigenous peoples‟ rights. They assist policy analysis through learning from the successes and failures of other jurisdictions in improving legal reform.